Netnography : doing ethnographic research online - Kozinets, Robert V., 1964-
The author also surveys the latest research on online cultures and communities, focusing on the methods used to study them. The research overview and procedural approaches are explained throughout with examples that include the latest developments in the social web, such as blogging, microblogging (tweeting), social networking, videocasting, podcasting, virtual worlds and more."--pub. desc.